Safeguarding Banks and Containing Property Booms : Cross-Country Evidenceon Macroprudential Policies and Lessons From Hong Kong SAR - Nabar, Malhar (IMF Working Papers; Working Paper, 2011)
We assess the effectiveness of macroprudential policies against a number of different indicators of property sector activity and financial stability. At the cross-country level the use of LTV caps decelerates property price growth. Both LTV and DTI caps slow property lending growth. LTV caps also affect a broader range of financial stability indicators in economies with pegged exchange rates and currency boards. For Hong Kong SAR, LTV policy tends to be forward looking, with caps lowered to counter downward movements in mortgage rates, and higher growth in mortgage loan and volumes of transactions. The reduction in caps appears to respond to small and medium size flat price appreciation, and contributes to a decline in high-end volume growth after a year and total transactions volume growth after 1 1\2 ?2 years. Price growth responds favorably after 2 years. The evidence suggests LTV tightening could affect property activity through the expectations channel rather than through the credit channel.